THE MAIN SIGNS OF DYSARTHRIA AS A SPEECH DISORDER - Iminjonova Mokhichehra Alimardon kizi (DEVELOPMENT OF EDUCATION AND SCIENCE IN THE ERA OF DIGITAL TRANSFORMATION, 2026)
This article examines the causes of dysarthria, its pathophysiological basis, and the main clinical signs affecting the speech system from a scientific and theoretical perspective. Dysarthria is a complex speech disorder caused by damage to the central and peripheral nervous systems, characterized by profound changes in articulation, phonation, breathing, prosody, resonance, and diction. The article presents a comparative analysis of differential features characteristic of spastic, flaccid, ataxic, hyperkinetic, and mixed forms of dysarthria, as well as the main speech therapy and neurological diagnostic criteria used in its diagnosis. The impact of dysarthria on speech development, phonetic and lexical-grammatical processes is also explored in detail. The research findings have practical significance for speech therapists, special educators, and neurologists working with dysarthria.